Answers

2015-09-20T02:04:20+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
A progressive wave with a uniform velocity v, angular frequency ω, wavelength λ and wave number k that is travelling in the positive x direction is given by:

      y₁(x, t) =  displacement of particle at x at time t = A Sin (k x - ω t)
                   k = 2π/λ

Let another progressive wave of equal magnitude, frequency, wave number also travel in the same medium, but in the negative x direction.
 
     y₂ (x, t) = A Sin (k x + ω t)

When both waves interfere, the resultant displacement of particles is:
     y(x, t) = A [ Sin (k x+ ω t) + Sin (k x - ω t) ]
               = (2 A  Sin k x ) Cos ωt

The effect of two equal waves in opposite directions is that the amplitude at each value of x is fixed in time.  Amplitude of the vibrating particles in the wave = 0  when k x = n π, where n is an integer.  Amplitude is maximum when  k x = (n + 1/2) π.

Since all the elements in the medium oscillate with same phase, move all synchronously and have fixed positions in space, they are called standing or stationary waves.

nodes = points where amplitude of oscillation = 0,   ie., k x = n π
           k  = 2 π/λ          x = n λ / 2          here n = 0,1,2,3,4,5...

antinodes = points where amplitude =  maximum :    ie., x = (n +1/2) π
                         x= (n + 1/2) λ/2            here n = 0,1,2,3,4
====================================
Suppose the second wave is a wave reflected from an obstruction that the progressive wave encounters on the medium.  It has a phase difference of π.

      y₁ (x, t) = A Sin (k x + ω t)
      y₂ (x, t) = A Sin (k x - ω t - π)  = A Sin (ω t - k x)
  
Superposition gives,   y(x, t) = A Sin ωt  *  Cos kx

Thus standing waves of same nature will result.  Nodes and antinodes will be interchanges as compared to the above.
   Nodes       x = (n+1/2) λ/2
   anti nodes    at  x = n λ/2 
1 5 1
click on thanks button above please
select best answer pls